A reference grammar of modern standard Arabic - Ryding, Karin C (Cambridge University, 2013)
A Reference Grammar of Modern Standard Arabic is a comprehensive handbook on the structure of Arabic. Keeping technical terminology to a minimum, it provides a detailed yet accessible overview of the language in which the essential aspects of its phonology, morphology and syntax can be readily looked up and understood.